Forest-based livelihoods strategies conditioned by market remoteness and forest proximity in Jharkhand, India - Belcher, B.; Achdiawan, R.; Dewi, S. (Elsevier, 2015)
The study uses a novel method to investigate the role of forest proximity, market remoteness, and caste in determining household income, especially forest income, in an underdeveloped region of India. A high (>50%) proportion of total income is earned in cash. Forest products contribute substantially to total income, with fuelwood as the most important forest product. Proximity to forest is associated with higher forest incomes as expected, but remote villages do not have higher forest incomes or lower cash incomes than less remote villages. Higher off-farm income is associated with better road access and higher income households generally.